SIMBOL-SIMBOL DALAM UPACARA MINUM TEH (TEA PAY) PADA PERNIKAHAN ETNIS TIONGHOA DI MANADO ( SUATU ANALISIS SEMIOTIK) - MOCODOMPIS, LISA OCTAVIN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is aimed to identify, classify, and analyze the symbols in Tea Ceremony of Chinese Ethnic Marriage in Manado. The data were collected by getting some information from informants. The identification and classification of the data are based on Peirce theory about semiotics in this case symbol, and the analysis used is descriptive method using Leech’s meaning theory. The problems in this research what the verbal and non-verbal symbols are and what the meanings of those symbols in Tea Ceremony of Chinese Ethnic Marriage in Manado are. The result of the research show that there are 14 symbols such as character symbol, word symbol, sentence symbol, color symbol, tea symbol, dragon and phoenix symbol, peony flower symbol, angpao symbol (red envelope symbol), two cups on the tray symbol, the respect symbol, giving the tea symbol, drink the tea together symbol, giving the angpao (red envelope) symbol, and giving the jewelry symbol. These symbols include verbal and non-verbal symbol and the meanings of these symbols are conseptual meaning and connotative meaning. Keywords: Symbols, Verbal and Non-Verbal Symbols, Conseptual and Connotative Meaning.